Beyond challenges: Opportunities for enhancing group work field education. - Skolnik, Sari; Skolnik, Louise (Social Work with Groups)
This paper focuses on opportunities for enhancing field education for group work practice. Five challenges influencing effective learning are reviewed and problem-solving strategies to cope with each are proposed. The challenges addressed are the generalist curriculum, inadequate preparation of field educators, agency prescribed co-leadership assignments, proliferation of manual based practice, and expanding use of online groups. The authors discuss specific strategies for meeting these challenges and for providing students with a field experience that teaches them to understand, appreciate, and practice social work with groups